Strategies to facilitate the integration of Hispanic migrants in a tourism-dependent community. Issue 1 (2nd January 2021) - Knollenberg, Whitney; Brune, Sara; Harrison, Jane; Savage, Ann
ABSTRACT: Tourism employers and tourism-dependent communities have come to rely on migrants to fill the considerable labor needs of the tourism industry. However, migrants are not always well integrated into the communities that they support, leaving them, the tourism industry, and tourism-dependent communities vulnerable. Set in a community where migrants have been welcomed and well integrated this study utilized in-depth interviews and focus groups with migrants, residents, tourism business owners, and policymakers to identify strategies that have helped Hispanic migrants integrate into a tourism-dependent community. Analysis of this qualitative data was guided by the social exclusion framework. This analysis revealed how economic, social, political, and cultural dimensions play a role in migrants' integration into the community. The findings reveal the importance of applying a multidimensional approach to integrating migrants into tourism-dependent communities—e.g. language, an element of the social dimension, facilitated activities related to the political dimension. Based upon these findings multiple strategies for integrating migrants into tourism-dependent communities are presented. These strategies move the literature beyond a descriptive identification of the challenges migrants face in integrating into tourism-dependent communities. Such strategies provide opportunities for tourism-dependent communities to improve the well-being of the tourism industry through the well-being of migrants.